Investigasi Forensika Digital WhatsApp Scam dengan Menggunakan Framework D4I - Nurdin, Rusydi; Ramadhani, Erika (Universitas Multi Data Palembang, 2024)
WhatsApp is an application that is very well known in Indonesia and the world. The WhatsApp application is also known to be one of the applications with the most users to date. This application can make it easier for us to communicate remotely to help with work matters. With the many conveniences provided by WhatsApp in terms of communication, there are many modes of crime that use WhatsApp as a tool to commit digital crimes, one of which is WhatsApp Scam. One of the actions that can be taken to find out the perpetrators and how the perpetrators commit fraud is by digital forensics investigation. Digital forensics is a part of forensic science with the scope of material (data) investigations and discoveries on digital devices such as smartphones, computers, tablets, storage, and other networked devices. It includes the application of informatics for the presentation of evidence data from computer crimes that can assist the court in cybercrime evidence with a focus on maintaining integrity and maintaining a tight chain of custody. The D4I framework is expected to improve the implementation of digital forensics investigations at the stage of examining data and analyzing existing data. The investigation was carried out by combining the National Institute of Standards and Technology (NIST) method and artifacts from the cyber kill chain (CKC) to assist in the digital forensics process.